Analisis Hubungan Komitmen Organisasi dan Disiplin Kerja terhadap Kinerja Pegawai Pemerintah Kota Makassar - Tri Fira Yuniza; Anna Ashrawi Suhartini (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2022)
The quality of an organization's performance is seen in a quality structure, especially in the commitment that is born from all elements of the organization, and work disciplines that become habits and culture. This study aims to determine and analyze the relationship between organizational commitment and work discipline on the performance of government employees in the city of Makassar simultaneously, and partially to achieve the target. The object of this research is the financial management employee at the SKPD in the city of Makassar with 60 respondents. The data used in this study is primary data obtained from employees through the distribution of questionnaires at the SKPD office in Makassar City. The analytical method of this research is a quantitative approach (Quantitative approach) with the help of the SPSS statistical program. The results of this study indicate that discipline partially has a positive and significant effect on the performance of financial management employees at SKPD in Makassar City. Where organizational commitment and work discipline have a positive and significant value on the performance of financial management employees at SKPD in Makassar City.